2015
DOI: 10.1007/s00374-015-1018-z
|View full text |Cite
|
Sign up to set email alerts
|

N2O emissions from banana plantations in tropical China as affected by the application rates of urea and a urease/nitrification inhibitor

Abstract: In this study, we quantified N 2 O fluxes from banana plantations in China using a field experiment as well as static chamber and gas chromatography techniques. We utilized five levels of urea treatments, including CK (no urea addition); urea addition at a rate of 312 (U1), 415 (U2), 519 (U3), and 623 kg N ha −1 (U4); and a combination of urea (U3) and urease (NBPT) and nitrification (DCD) inhibitor (U3 + I) treatments. Soil temperature, moisture, and the concentrations of NH 4 + and NO 3 − have been monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
4
12
0
Order By: Relevance
“…Globally, soils a r e m a j o r s o u r c es o f N 2 O e m i s s i on s , a n d 60 % (3.5 Tg N year −1 ) of N 2 O emissions are derived from arable soils (Goldberg and Gebauer 2009;IPCC 2013). There is little doubt that increasing atmospheric concentration of N 2 O is primarily caused by the excessive use of nitrogen (N) fertilizer (Davidson 2009;Shcherbak et al 2014;Zhu et al 2015). However, N 2 O production from N fertilizer depends mainly on soil properties but also by soil moisture and the type of N fertilizer (Zhu et al 2013b;Cheng et al 2014;Wang et al 2016a;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, soils a r e m a j o r s o u r c es o f N 2 O e m i s s i on s , a n d 60 % (3.5 Tg N year −1 ) of N 2 O emissions are derived from arable soils (Goldberg and Gebauer 2009;IPCC 2013). There is little doubt that increasing atmospheric concentration of N 2 O is primarily caused by the excessive use of nitrogen (N) fertilizer (Davidson 2009;Shcherbak et al 2014;Zhu et al 2015). However, N 2 O production from N fertilizer depends mainly on soil properties but also by soil moisture and the type of N fertilizer (Zhu et al 2013b;Cheng et al 2014;Wang et al 2016a;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce potentially increased ammonia volatilization after application of nitriication inhibitors, manufactures developed urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT) [56,57]. Application of NBPT has been proved efective in reducing pasture soil urease activity and mitigating ammonia volatilization [58,59].…”
Section: Chemical Nitriication Inhibitorsmentioning
confidence: 99%
“…Application of NBPT has been proved efective in reducing pasture soil urease activity and mitigating ammonia volatilization [58,59]. The combination of nitriication inhibitor and NBPT could also decrease the yield-scaled N 2 O emissions relative to treatments only with fertilizer in banana plantations [56].…”
Section: Chemical Nitriication Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found a high N retention capacity in the highly weathered soils of natural forests in subtropical or tropical regions, which exhibit high gross mineralization rates along with low gross nitrification rates [11,13]. During the conversion of forest to farmland, an input of N, preferentially provided in inorganic form, as well as frequent irrigation and tillage can greatly change the soil properties and biochemical environment (e.g., soil organic matter, water holding capacity and pH) [20][21][22][23], which may affect mineralization and nitrification rates, and N availability in soils. At the initial stage of banana cultivation via conversion from forests, tillage can increase the soil's porosity and subsequently the O 2 diffusion into the soil, which could increase microbial abundance and activity, thus accelerating the decomposition of soil organic matter [24], suggesting a possible increase in mineralization rate.…”
Section: Introductionmentioning
confidence: 99%